Persebaran Wilayah Rentan Terdampak Perubahan Iklim Global di Kabupaten Lombok Tengah - Clara Bilqis Florissa; Adi Subiyanto; Christine Sri Marnani; Pujo Widodo; Herlina Juni Risma Saragih; Kusuma (Jurnal Kewarganegaraan, 2022)
Abstract This study about distribution of vulnerability area climate change impacts in Central Lombok, Indonesia. The design of research is used descriptive methods and qualitative research types. Spatial planning is closely related to disaster. Indonesia is a region that is very vulnerable to disasters, therefore in the preparation of spatial planning must always refer to the potential dangers or threats that exist in an area. One of the disasters that currently threatens Indonesia is climate change. Climate change is a problem that is faced by all people in the world, including Indonesia. Indonesia is an archipelago state, this situation makes Indonesia very vulnerable to the negative impacts of climate change. Climate change not only impacts the environment, but also has a direct impact on human life. Central Lombok is located on a small island which makes its territory more vulnerable to the impacts of climate change. Keywords: Climate Change, Disaster, Spatial Planning, Impact.